Optimizing Regulations in Public Services: A Compliance and Risk Management Approach - Tekat Sukomardojo; Rahmat Purbandono; Alex Irawan Triyantho; Wahyu Prianto; Rini Dwiastutiningsih (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Meeting the needs of the general public can be met by public services. Therefore, there is a need for public services that are efficient, effective and fair. In achieving this goal, various challenges arise in optimizing good public services. This research then aims to look at how to optimize regulations in public services through a compliance and risk management approach. This research was carried out using a qualitative approach. The data in this research uses various results of previous research and studies. The results of this research then found that an approach that includes compliance, risk management, and regulatory performance evaluation is an important element in the government's efforts to provide better public services to the community. This integration creates a better environment for public services that are efficient, effective, fair and responsive to change. Accuracy in designing regulations, measuring effectiveness, and playing a role in improvement is the key to achieving optimal public service goals. With this holistic approach, the government can meet people's expectations and help create a more prosperous society.